Using ChatBot-Based Artificial Intelligence (AI) for Writing an English Essay: The Ability of ChatGPT, Perplexity AI, and ChatSonic - Fitria, Tira Nur (Journal of Language Intelligence and Culture, 2024)
This study investigates the effectiveness of advanced AI chatbots, including ChatGPT, Perplexity AI, and ChatSonic, in generating argumentative essays. Employing a descriptive qualitative approach, the research analyzed data collected through document review. In-depth analysis revealed that these AI chatbots are highly capable of producing persuasive essays. The chatbots generate text that aligns with the given topic by responding to specific prompts. The more detailed the prompt, the more relevant and informative the generated content. Additionally, ChatGPT and Perplexity AI offer valuable writing tips and even suggest online resources for further assistance. However, it is essential to acknowledge the limitations of AI and balance their use with human development and the cultivation of student writing skills.